Six new species of the genus Bellulia Fibiger, 2008 from China and Cambodia (Lepidoptera, Erebidae, Hypenodinae). Taxonomic study of Micronoctuini. Contribution III - Han, Hui Lin; Kononenko, Vladimir S. (Zootaxa, 2021)
Six species of the genus Bellulia Fibiger, 2008: B. tenebrosa sp. n., B. clara sp. n., B. jiaxuanae sp. n., B. jiayiae sp. n., B. fuscis sp. n. and B. diannana sp. n. are described from China and Cambodia. Two species, Bellulia suffusa Fibiger, 2008 and B. basalia Fibiger, 2010 are reported for the first time from Cambodia. Keys for identifying species in the kareni, bella and suffusa species-groups and a complete checklist of the genus Bellulia are presented.